Implementation Of Collection Of Land And Building Rights Acquisition Duty (BPHTB) In Terms Of Transfer Of Land Rights In Trenggalek Regency - Dwi Fahrizal, Dian (Universitas Islam Malang, 2023)
Abstract : The increase in development activities in all fields has led to an increase in the need for available land and or buildings. Meanwhile, land and/or building supplies are very limited. Given the importance of land and or buildings in life, it is natural that individuals or legal entities who get economic value and benefits from land and or buildings due to the acquisition of land and or building rights are taxed by the state. The tax in question is Land and or Building Rights Acquisition Duty (BPHTB). Land and Building Rights Acquisition Duty (BPHTB), is a tax imposed on the acquisition of land and building rights. Based on the things mentioned above, the problems that will be examined in this study are: How is BPHTB collected on land and or building sale and purchase transactions, What is the role of PPAT in BPHTB collection, and what obstacles arise in BPHTB collection and how to overcome them. The approach method used is an empirical juridical approach and the specifications used in this study are analytical descriptive research. Based on the results of the study, it can be concluded that BPHTB in its implementation uses an official self assessment system whose magnitude is determined from the aprisial results by BAKEUDA Trenggalek Regency. PPAT has a significant role in collecting BPHTB because PPAT is a general official related to transactions on the transfer of land rights, PPAT will sign an authentic deed after the BPHTB tax is paid in full by the Taxpayer. The Land Deed Making Officer can only sign the deed of transfer of title to land and or buildings after the Taxpayer submits proof of tax payment. Land Deed Making Officials who violate the provisions mentioned above are subject to administrative sanctions in the form of a fine of IDR 7,500,000.00 (seven million five hundred thousand rupiah). In addition, PPAT also plays a role in helping Taxpayers calculate the amount of BPHTB.Keywords: Implementation of Collection, Land Rights Acquisition Duties,